(untitled) (Revista de Física Médica, 2023)
An in-house software to automate the volumetric modulated arc therapy treatment planning using the Varian Eclipse radiotherapy planning system is presented. It performs the entire planning process with very little human interaction. It interprets the clinical prescription and translates it into optimization objectives, creates auxiliary anatomical contours, and optimizes the plan to achieve proper dose distributions. The application allows the simultaneous processing of several plans. To evaluate the performance of the software, several already treated plans from different anatomical localizations were randomly chosen, re-planned using this automated tool and compared. The difference between planned and prescribed dose was studied for all dose constraints. Automated plans obtained better results in more than half the prescribed dose limits for almost all locations. The total time required to carry out the plans was also determined. It can be concluded that automated planning is quick and take less time than manual planning in most cases, but the main point is that automatic planning requires almost no human attention. Automatic treatment planning can free up many staff hours, reduce the experience required, smooth the learning curve for this complex technique, decrease the subjective decisions and therefore increase the homogeneity in patient treatments.